Experimental study of partially oxidized sodium alginate gel combined with myogenic stem cells to improve cardiac function in aged rats with myocardial infarction - Xinxin Ma; Xiaolu Hou; Peixin Dong; Jiayan Ye; Yangyang Gao; Ling Huang; Xiuping Bai (Guoji laonian yixue zazhi)
[Objective] To investigate the effect of partially oxidized sodium alginate gel combined with intramyocardial injection of myogenic stem cells on cardiac function in aged rats with myocardial infarction. [Methods] The models of myocardial infarction in aged rats were established by ligating the coronary arteries and divided randomly into the group of saline control group, sodium alginate group, myogenic stem cells group and sodium alginate combined with myogenic stem cells group(joint group), each had 30 rats.The same amount of corresponding material was injected into the myocardial infarction area of rats in each group respectively.The cardiac structure and function of the rats were evaluated by echocardiography 8 weeks after the operation, and then the rats were executed.The hearts were removed to observe the differences in ventricular remodeling by histological analysis and the angiogenesis and collagen secretion of the ventricular slices were further analyzed. [Results] The echocardiographic indexes, histological indexes, vessel density per unit area, and the percentage of collagen-positive area in the rats of the joint group were better than those in the other groups (P<0.05).The echocardiographic indexes, histological indexes, vessel density per unit area, and the percentage of collagen-positive area in the rats of sodium alginate group and myogenic stem cell groups were better than those in the saline control group (P<0.05), while there was no statistic difference between the sodium alginate group and myogenic stem cells group(P>0.05). [Conclusion] Sodium alginate gel combined with intramyocardial injection of myogenic stem cells can significantly improve the cardiac function in aged rats with myocardial infarction, which also shows the better effects than the injection of sodium alginate or myogenic stem cells separately.